2012
DOI: 10.1161/hypertensionaha.111.185520
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Causes Mineralocorticoid Receptor Activation in Rat Cardiomyocytes

Abstract: Abstract-Overactivation of the mineralocorticoid receptor signaling is implicated in cardiovascular disease, including hypertensive heart disease. Oxidative stress is suggested to augment mineralocorticoid receptor signal transduction, but the precise mechanisms remain unclear. Mineralocorticoid receptor activity is regulated by multiple factors, in addition to plasma ligand levels. We previously identified Rac1 GTPase as a modulator of mineralocorticoid receptor activity.Here we show that oxidative stress ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
51
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 44 publications
4
51
0
1
Order By: Relevance
“…They found that L-buthionine sulfoximine (BSO), which depletes intracellular glutathione, increased the active form of Rac1, and this effect was blocked by the antioxidant N-acetylcysteine (NAC). 119 Consistent with their findings with BSO, H 2 O 2 also activated Rac1. 119 Similarly, H 2 O 2 treatment led to a robust increase in GTP-bound Rac1 in neutrophils derived from C57/BL6 control mice.…”
Section: Redox Regulation Of Racsupporting
confidence: 86%
See 1 more Smart Citation
“…They found that L-buthionine sulfoximine (BSO), which depletes intracellular glutathione, increased the active form of Rac1, and this effect was blocked by the antioxidant N-acetylcysteine (NAC). 119 Consistent with their findings with BSO, H 2 O 2 also activated Rac1. 119 Similarly, H 2 O 2 treatment led to a robust increase in GTP-bound Rac1 in neutrophils derived from C57/BL6 control mice.…”
Section: Redox Regulation Of Racsupporting
confidence: 86%
“…119 Consistent with their findings with BSO, H 2 O 2 also activated Rac1. 119 Similarly, H 2 O 2 treatment led to a robust increase in GTP-bound Rac1 in neutrophils derived from C57/BL6 control mice. 120 Chronic exposure of normal mouse mammary gland epithelial (NMuMG) cells to H 2 O 2 not only elevated Rac1 activity but also greatly enhanced cell invasiveness.…”
Section: Redox Regulation Of Racsupporting
confidence: 86%
“…These findings are compatible with our previous observation in cultured cardiomyocytes that overexpression of active Rac1 induced MR activation in a ligand-independent manner in cells cultured with serum-depleted medium or when the cellular MR gene was replaced with a ligand-resistant mutant. 18 Given that the ligand binding of MR in cardiomyocytes is already saturated at steady state by the absence of 11β-HSD2, Rac1 serves as an enhancer of MR activation via increased nuclear MR translocation in the pressure-overloaded heart, in a similar manner to the essential role for Rac1 in the nuclear localization of β-catenin, a transcription factor involved in canonical Wnt signaling. 35 Aberrant Rac1-mediated MR activation in the myocardium was supported by changes in the expression of various target genes of MR in the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac myocyte-specific overexpression of an active form of Rac predisposes the heart to postischemic contractile dysfunction (Talukder et al, 2013). Through activation of NADPH oxidase, Rac1 activation contributes to oxidative stress, which promotes cardiac injury and dysfunction (Maack et al, 2003;Endou et al, 2004;Elnakish et al, 2012;Nagase et al, 2012;Zhang et al, 2012;Ma et al, 2013). Moreover, Rac1 is essential for the hypertrophic response in the heart (Sussman et al, 2000;Satoh et al, 2006;Vettel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%